Molecular study of extended-spectrum beta-lactamase (TEM-1) gene in Escherichia Coli isolates collected from Ostad Alinasab Hospital in Tabriz Iran - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objectives: Emergence of antibiotic resistance is an important problem in microbial infection control. Certain enzymes can lead to resistances against the third generation cephalosporins by the hydrolysis of monobactams. This study was conducted to evaluate antibiotic sensitivity profiles and the presence of bla TEM gene in E. coli isolates collected from clinical specimens of Ostad Alinasab Hospital in Tabriz. Materials and Methods: E. coli (100 isolates) were detected by using conventional bacteriologic tests and then antibiotic sensitivity tests were performed according to Kirby-Bauer method. Confirmatory test was also performed by combined disk test method. Finally bla TEM gene was detected by using polymerase chain reaction (PCR) technique. Results: Our fo 100 E. coli 23% of isolates contained bla TEM gene. 18% of isolates were resistant to ceftazidime, while 30% of isolates were resistant to cefotaxime and the remaining was sensitive. 46% of isolates were ESBL producers from which 23% of them contained bla TEM gene. Conclusion: High resistance of E. coli isolates to the third generation cephalosporins underlines need for accurate sensitivity tests, also avoidance from inappropriate use of antibiotics.
Keywords: Extended-spectrum beta-lactamases (ESBLs); bla(TEM) gene; Escherichia coli; Polymerase chain reaction